Adsorption enhanced photocatalytic degradation of Rhodamine B using GdxBi1-xFeO3@SBA-15 (x= 0, 0.05, 0.10, 0.15) nanocomposites under visible light irradiation. Issue 20 (15th October 2021) - Cadenbach, Thomas; Benitez, Maria J.; Tirado, Sofia Andrade; Ochoa-Herrera, Valeria; Debut, Alexis; Vizuete, Karla
Abstract: BiFeO3 nanomaterials have recently generated much interest due to their relatively narrow band gap energies (~2.0–2.8 eV), their stability and low cost which leads to effective visible-light photocatalysts for water splitting and for the degradation of organic pollutants. Here, we show that very high removal efficiency of the organic dye Rhodamine B can be achieved using Gdx Bi1-x FeO3 @SBA-15 nanocomposites (x = 0, 0.05. 0.10, 0.15) under visible light irradiation. Specifically, we study the photocatalytic degradation of Rodamine B using the above nanocomposite materials, with pore volume loadings of 5–25%, prepared by a wet-impregnation nanocasting technique with pre-fabricated metal tartarates, as metal precursors, and mesoporous silica SBA-15, as a host matrix. We find that the best removal performance is achieved by a 10 vol% Gd0.05 Bi0.95 FeO3 @SBA-15 sample, shown by a complete dye degradation in approximately 3 h using very low concentrations of the actural active photocatalyst. The superior efficiencies of the nanocomposites, which outperformed their parent compounds, i.e. Gdx Bi1-x FeO3 nanoparticles as well as unfilled SBA-15, are attributable to a synergistic adsorption enhanced photocatalytic degradation process. The possible mechanism in the photodegradation process was investigated and discussed on the basis of trapping experiments.